Adolescents' face mask usage and contact transmission in novel Coronavirus - Fang-Lin Chao (SAGE Publishing, 2020)
The global outbreak of coronavirus has become an international public health threat. Prevention is of paramount importance to contain its spread. This study observes face mask wearing behavior and contact transmission problems in Taiwan. Teachers track student status in class. In addition to measuring body temperature and regular disinfection, classrooms require ventilation wear mask, provide alcohol spray and avoid sharing the microphone. Both questionnaire surveys and experimental were utilized. A total of 160 adults residing in Taiwan participated in the survey. The dye simulated the possible virus area on the mask surface during usage. Subjects were required to complete a questionnaire and simulate the spread of contact transmission when using a computer. Eighty-one % of respondents reported consistent use of surgical masks several times a day. They reported taking their masks off in relatively safe areas. Most people reported using one mask per day and storing the masks in their pockets. As a result, masks surface become a contamination source. In the contact experiment, ten adults were requested to don and doff a surgical mask while doing a word processing task. The extended contamination areas were recorded and identified by image analysis. The results show an average contamination area of the workspace is significant 530 cm2. When the hand touches the surface of the mask, it may spread the virus to the subsequent contact area.